Analysis of Legal Basis in Education: Study of Law, Policy and Deviance in Education - Nasrul Syakur Chaniago; Refi Syahputra; M. Amri Nasution; Fahrul Sanawi; Amiruddin Siahaan; Inom Nasution (AL-ISHLAH: Jurnal Pendidikan, 2023)
The low quality of Indonesia's human resources (HR) is caused by irregularities (non-compliance with regulations and implementation) that occur in the process of providing education. This study aims to analyze the legal basis in the field of education and its implementation in Indonesia. The formulation of the research problem includes how the foundations and policies of education in Indonesia are and how the legal position (specifically in the field of education) is in hacking educational irregularities. This study uses an approach to the literature study method in the form of Preferred Reporting Items for Systematic Review (PRISMA). A systematic literature review is systematic by collecting some relevant evidence according to specified criteria to answer several questions. The results of this study conclude that enacting laws, government regulations and regulations of the minister of education regarding the "legal umbrella" of education policy has become a positive step for fulfilling people's rights. However, the reality in society is that there are still deviations in management, behavior and code of ethics during the implementation of the educational process, including the practice of cheating by individual units of educational institutions in graduating students to meet student graduation standards according to Permendikbud No. 23 of 2006, the unpreparedness of schools or madrasas to facilitate the rights of students with disabilities in accordance with education management standards (Permendikbud no. 19 of 2007), determination of individual principals based on bribery practices that violate Permendikbud no. 13 of 2007 concerning school principals, and marginalization of treatment of education in schools. remote areas that violate PP number 19 of 2005 on national education standards. Likewise, the limitations of researchers have not explored this study from the psychological aspect of education, namely the discussion of self-welfare and soft skills of students due to educational deviations.